Gas sensing properties of zinc stannate (Zn2SnO4) nanowires prepared by carbon, assisted thermal evaporation process - Tharsika, T.; Haseeb, A.S. Md. Abdul; Akbar, S.A.; Sabri, M.F.M.; Wong, Y.H. (2015)
Zn2SnO4 nanowires are successfully synthesized by a carbon assisted thermal evaporation process with the help of a gold catalyst under ambient pressure. The as-synthesized nanowires are characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM) equipped with an energy dispersive X-ray spectroscopy (EDS). The XRD patterns and elemental mapping via TEM-EDS clearly indicate that the nanowires are Zn2SnO4 with face centered spinel structure. HRTEM image confirms that Zn2SnO4 nanowires are single crystalline with an interplanar spacing of 0.26 nm, which is ascribed to the d-spacing of (3 1 1) planes of Zn2SnO4. The optimum processing condition and a possible formation mechanism of these Zn2SnO4 nanowires are discussed. Additionally, sensor performance of Zn2SnO4 nanowires based sensor is studied for various test gases such as ethanol, methane and hydrogen. The results reveal that Zn2SnO4 nanowires exhibit excellent sensitivity and selectivity toward ethanol with quick response and recovery times. The response of the Zn2SnO4 nanowires based sensors to 50 ppm ethanol at an optimum operating temperature of 500 degrees C is about 21.6 with response and recovery times of about 116 s and 182 s, respectively. (C) 2014 Elsevier B.V. All rights reserved.